1999
DOI: 10.1115/1.2798047
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Graft Caliber Upon Wall Shear Within in Vivo Distal Vascular Anastomoses

Abstract: Wall shear has been widely implicated as a contributing factor in the development of intimal hyperplasia in the anastomoses of chronic arterial bypass grafts. Earlier studies have been restricted to either: (1) in vitro or computer simulation models detailing the complex hemodynamics within an anastomosis without corresponding biological responses, or (2) in vivo models that document biological effects with only approximate wall shear information. Recently, a specially designed pulse ultrasonic Doppler wall sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Graft-host diameter ratio can influence graft hemodynamics at end-to-side anastomoses substantially [2-4]. In a computational simulation model of CABG, Qiao et al reported that large graft-host diameter ratio (1.46) produces better hemodynamics than equal or small (0.8) ratio when the diameter of a target vessel is assumed to be 2.5 mm [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graft-host diameter ratio can influence graft hemodynamics at end-to-side anastomoses substantially [2-4]. In a computational simulation model of CABG, Qiao et al reported that large graft-host diameter ratio (1.46) produces better hemodynamics than equal or small (0.8) ratio when the diameter of a target vessel is assumed to be 2.5 mm [5].…”
Section: Discussionmentioning
confidence: 99%
“…Spivack et al reported that the mean diameter of the great saphenous vein (GSV), which is commonly used for sequential CABG, is between 2.3 mm to 4.4 mm [1]; while the average diameter of small target coronary arteries of Chinese patients is usually 1 mm. Graft-host diameter ratio has been shown to influence distal anastomotic hemodynamics and consequently graft patency [2-4]. Although large graft-host diameter ratio has been shown to have better hemodynamic performance than smaller ones under end-to-side anastomoses [5], the oversize diameter ratio between the GSV and small target coronary arteries might induce adverse hemodynamics condition and compromise graft patency.…”
Section: Introductionmentioning
confidence: 99%
“…Generalized 49 and system specific 20,38 observations of IH localization have been shown to correlate with regions of low wall shear stress (WSS) and high oscillatory shear index (OSI) 3,21,22,38,42 as well as with variations in the WSSfield as determined by the WSS-gradient (WSSG) 25,51 and WSS-angle-gradient (WSSAG). 24 Intimal hyperplasia along the suture-line is widely associated with surgical injury, suture technique, compliance mismatch, and intramural strain.…”
Section: Introductionmentioning
confidence: 98%
“…Unfortunately, quite often the quality of the vessel anastomosis is not very satisfactory and may decrease significantly over time. Consequently, many researchers seek approaches to ensure the quality of anastomosis by adjusting the appropriate values of process variables (22)(23)(24)(25)(26)(27). However, most of them focus on the wall shear stress distribution that may induce intimal hyperplasia and thrombosis, hence ultimate failure in anastomosis.…”
Section: Introductionmentioning
confidence: 99%